Hubungan Persepsi Alumni Fakultas Pertanian dan Bisnis Universitas Kristen Satya Wacana Terhadap Pekerjaan di Sektor Pertanian dengan Minat Bekerja di Sektor Pertanian - Sirenden, Mutiara; Zebua, Damara Dinda Nirmalasari (Universitas Galuh, 2026)
The sustainability of the agricultural sector today is the regeneration of farmers, by rebuilding the successors of agriculture, namely the younger generation, in future farming activities. The objectives of this study are 1) to analyze the level of perception of alumni of the Faculty of Agriculture and Business, Satya Wacana Christian University (FPB UKSW) regarding work in the agricultural sector; 2) to analyze the level of interest of FPB UKSW alumni to work in the agricultural sector; and 3) to analyze the relationship between the perception of FPB UKSW alumni towards work in the agricultural sector and their interest in working in the agricultural sector. This type of research is quantitative descriptive with sampling using simple random sampling techniques. The data analysis technique in this study uses scoring with three categories to analyze perceptions and interests as well as Spearman Rank correlation analysis to analyze the relationship between variable (X) and the dependent variable (Y). The results of the study show that 1) the level of perception of UKSW FPB alumni regarding work in the agricultural sector is in the moderate category, namely 62%; 2) the level of interest of UKSW FPB alumni to work in the agricultural sector is in the moderate category, namely 68%; and 3) the relationship between the perceptions of UKSW FPB alumni regarding work in the agricultural sector and their interest in working in the agricultural sector is significantly correlated (<0.001) and strongly positive with a correlation coefficient value of 0.761. This means that the more positive the perception of UKSW FPB alumni towards work in the agricultural sector, the higher the interest in working in the agricultural sector.